Financial transaction taxes: Announcement effects, short-run effects, and long-run effects - Sebastian Eichfelder; Mona Lau (Arbeitskreis Quantitative Steuerlehre (arqus), 2016)
We analyze the impact of the French 2012 financial transaction tax (FTT) on trading volumes, stock prices, stock liquidity and volatility. We extend the empirical research by the identification of FTT announcement and short-run treatment effects, which may distort difference-in-differences estimates. In addition, we account not only for the intraday volatility but also for long-term volatility measures. While we find strong evidence for a positive FTT announcement effect on trading volumes, there is almost no statistically significant evidence for a long-run treatment effect. Thus, existing evidence on a strong reduction of trading volumes resulting from the French FTT might be biased by FTT announcement effects. We also find an increase of intraday volatilities in the announcement period and a significant reduction of weekly and monthly volatilities in the treatment period. Therefore, our findings support theoretical considerations suggesting a stabilizing impact of FTTs on financial markets. While some of our results suggest a reduction of stock prices in the announcement period, our results on bid-ask spreads and daily returns are not fully conclusive.
Keywords: G02; G12; H24; M41; 330; financial transaction taxes; market quality; volatility; trading volume; liquidity; price discovery; announcement effects; short-run treatment effects